(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study aims to identify the impact of using the infrastructure of the Information Technology (IT) on the performance of human resources in the public universities. This process is done by doing research in the size, quality, and efficiency of the performance, also speed of achievement and simplification of procedures. Diyala University was chosen for the diagnosis through the opinions and attitudes of its employees. Consequently, suggestions that contribute to improve the performance of the employees and thus its overall performance are obtained. Another objective of this study is identifying the human resources which are currently used in academic institutions and educational services systems because the significant role of these resources in the trend towards usage of technology in human resources management. The study considers various administrative and academic levels in the university community. The researchers used a questionnaire composed of (40 items) as a tool to study and descriptive analytical method in order to achieve the objectives of the study. The number of questionnaire forms which are used in the analysis is (83). The study includes a presentation of the theoretical and conceptual framework of the subject to find out its background theory. In addition, some previous studies are considered in order to determine the influencing variables in the problematic study, including two major assumptions. For the empirical framework, which is the embodiment of the theoretical framework in reality, a questionnaire is designed to collect data and information by taking samples fromDiyala University. Statistical methods were used to analysis the questionnaire data,test hypotheses,obtain conclusions and assess suggestions on the subject. The study found a relationship between the usage of the infrastructure for information technology and human resources performance.The relationship found to be 44.6 percent, based on the value of the correlation coefficient. This explainsthat the utilization of the infrastructure for information technology in DiyalaUniversity will improve the performance of human resource in terms of speed and accuracy of achievement.Moreover,it indicates the presence of the effect of using the infrastructure of information technology on the performance of employees by increasingservices,rate of the achieved work, accuracy, quality and efficiency.Also it will help canceling many proceduresand coordinate between the business, which is reflected on simplifying work.